Systemy informatyczne w administracji publicznej w Polsce : stan obecny i perspektywy rozwoju - Gryncewicz, Wiesława; Nowicki, Adam; Rot, Artur (Information systems in Polish public administration: the current state and prospects, 2005)
All levels of departments of Polish public administration from communes to the central authorities struggle against the same problems in the area of citizens’ service and support as the private sector met already a dozen years ago. Most public institutions are at present technologically not up to date, but very common interest in the Internet and other modem information technologies has resulted in the idea of e-government developing quickly and becoming widespread in Poland. In the article we will present some topics related to spreading the e-government concept in Poland. The current state of computerization of public administration institutions in Poland will be presented, and we will review the most common software solutions and present directions and perspectives of development in this area.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 50-60